Impact Resistance of High-Performance Steel Fiber Concrete under Long Term Exposure to Environmental Conditions - Abubakar, Abdulhameed Umar; Akcaoglu, Tulin; Marar, Khaled (E D P Sciences, 2018)
An investigation is presented here that studied the influence of long-term environmental conditions exposure on cylindrical specimens after initial 28 day moist curing. The specimens were tested after six months subjected to Mediterranean weather elements in North Cyprus. Specimens with 150 mm diameter by 60 mm long cylinders were tested under impact load using a modified version of the testing equipment described in ACI 544.2R. Numbers of blows to create first and damage cracks were determined, and subsequently the impact energies calculated. It was seen that there is as much as twenty times improvement in impact energy of fibered concretes at fiber volume of 2 % when compared with plain concrete. This will go a long way to improve the impact resistance of industrial floors and slabs on grade.
3rd International Conference on Civil Engineering and Materials Science (ICCEMS) -- APR 13-15, 2018 -- Chengdu, PEOPLES R CHINA
Keywords: Strength